2013
DOI: 10.1001/jamapsychiatry.2013.278
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Mortality in People With Mental Illness

Abstract: There is a 30% higher case fatality rate from cancer in psychiatric patients even though their incidence of cancer is no greater than in the general population. The reasons are unclear, but if increased cancer mortality were due to lifestyle only, cancer incidence should be similarly increased. Other hypotheses include delays in presentation, leading to more advanced staging at diagnosis, and difficulties in treatment access following diagnosis.Objective: To assess why psychiatric patients are no more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
299
7
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 287 publications
(343 citation statements)
references
References 51 publications
(99 reference statements)
19
299
7
7
Order By: Relevance
“…They are at increased risk for mortality due to many factors arising from their disability [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are at increased risk for mortality due to many factors arising from their disability [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies report a significantly higher rate of mortality in psychiatric patients overall compared to the general population [11][12][13], and one study has shown a higher rate of mortality for psychiatric patients with cancer even though the incidence of cancer in psychiatric patients is no greater than in the general population [11]. One possible explanation includes reduced access to screening [14,15], leading to delayed diagnosis and a more advanced stage at presentation.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…When we focused the analysis on high-risk patients with dementia, given the increasing attention to mental illness of terminally ill patients 23,24 , we found a higher prevalence of dementia among high-risk elderly patients (2.24% vs. 0.17% in the low-risk cohort, P<0.001). About 40% of high-risk patients took medications for mental illness health conditions, which substantially higher than in the low-(6.5%) and intermediate-risk (27.3%) groups.…”
Section: Risk Stratification and Clinical Patternsmentioning
confidence: 90%
“…The prevalence of using antipsychotic medication was high in nursing homes, while the substantial use of conventional antipsychotics was common in acute and long-term inpatient settings 34 . Hence, these findings should give rise to more attention to mental illness of terminally ill patients, not only because of higher fatality rate from cancer in psychiatric patients 23 , but also because of great opportunities to improve end-of-life care for these vulnerable patients, given their loss of ability to communicate need and severe physical consequence 35 .…”
Section: Interpretation Of Predictorsmentioning
confidence: 99%